2020
DOI: 10.1200/jco.2020.38.15_suppl.1010
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of ESR1 mutations in ER+ HER2- MBC patients prior treated with first line AI and palbociclib: An exploratory analysis of the PADA-1 trial.

Abstract: 1010 Background: The question of which is the best endocrine partner to CDK4/6 inhibitors in first line for ER+ HER2- metastatic breast cancer (MBC) remains open. ESR1 mutations might be of paramount importance, as they confer resistance to AI but not to SERD. In pts treated with first line palbociclib-AI combination (PADA-1 trial, NCT03079011), we investigated ESR1mut detection rate at inclusion, prior to any therapy, and their prognostic impact. Methods: The PADA-1 phase 3 trial (NCT03079011, UCBG-GINECO) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 0 publications
0
36
0
4
Order By: Relevance
“…genetic, and epigenetic characterization to better characterize the complexity of ET resistance (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…genetic, and epigenetic characterization to better characterize the complexity of ET resistance (34).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, 2 patients (8%) experienced a progression without the recurrence of ESR1 mutation. Since the study was based on a genetic-only characterization, these results suggest the need for a wider, genetic, and epigenetic characterization to better characterize the complexity of ET resistance ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not associate with long-term improvement in survival outcomes on fulvestrant alone relative to patients with wild-type ESR1 [ 75 ]. Recently, investigators reported the first results from the PADA-1 trial, in which the utility of monitoring the onset of ESR1 mutation in cell-free DNA from patients receiving first-line aromatase inhibitor combined with palbociclib is being evaluated [ 76 ]. Among the 1017 patients, 3.2% had a detectable circulating ESR1mut at inclusion.…”
Section: Detecting Dynamic Circulating Tumor Dna Alterations and Cmentioning
confidence: 99%
“…At the ASCO Symposium 2020 the results of two CDK4/6 trials were presented, which had studied ctDNA measurements in their translational adjunct programmes 55 , 56 . The PADA-1 trial evaluated the clinical significance of the ESR1 mutation detected in cell-free DNA of 1017 patients under treatment with aromatase inhibitors and palbociclib 56 . All patients presented with ER-positive, HER2-negative metastatic disease and received first-line treatment in the trial.…”
Section: Clinical Applications Of Liquid Biopsy In Metastatic Breast mentioning
confidence: 99%
“…Auf dem ASCO-Symposium 2020 wurden die Ergebnisse von 2 CDK4/6-Studien vorgestellt, die ctDNA-Messungen in ihren translationalen Begleitprogrammen untersucht hatten 55 , 56 . In der PADA-1-Studie wurde die klinische Bedeutung der in der zellfreien DNA detektierten ESR1-Mutation unter der Therapie mit Aromatasehemmer und Palbociclib bei 1017 Patientinnen evaluiert 56 . Alle Patientinnen hatten eine ER-positive HER2-negative metastasierte Erkrankung und erhielten die Erstlinientherapie im Rahmen der Studie.…”
Section: Therapiemonitoring Mittels Liquid Biopsyunclassified